Taxidermal Preparations of an Extinct Sicilian Wolf Population (Canis lupus Linnaeus, 1758): Biological Studies and Restoration - Stefano Reale; Valentina Cumbo; Silvia Scibetta; Ignazio Sammarco; Sabrina Lo Brutto; Antonio Spinnato; Salvatore Seminara (Springer, 2022)
In last decades, biotechnologies have enabled a deep development of knowledge in all fields of life sciences, allowing the collection of a wide range of data. Furthermore, the relationship between scientific investigations and conservation actions of cultural heritage is increasingly consolidated and now it is one of the peculiar points both for sustainable restoration and use of the cultural asset, also evaluating the cultural assets as source of biological information. In this study, Sicilian wolf (Canis lupus) specimens conserved in Sicilian Natural Museums, become a source of biological information on Sicilian biodiversity, establishing specific conservative protocol developed cooperatively with Sicilian Natural Museums. Using Next-Generation Sequencing technique, ancient DNA (aDNA) molecules extracted from nail were utilized to perform the complete mitochondrial DNA genome sequence. Phylogenetic analyses showed that this genome, which was aligned with a number of historical and extant complete wolf and dog mtDNAs sampled worldwide, was closely related to an Italian wolf mtDNA genome. These mtDNA findings suggest that wolves probably colonized Sicily from southern Italy toward the end of the last Pleistocene glacial maximum, when the Strait of Messina was almost totally dry. Furthermore, a conservative restoration of this peculiar natural specimen (taxidermal preparation) has been performed, basing on: recovery of unglued or unstitched parts; revitalization of the colors of the mucous membranes; restoration of deformed or broken parts of the body, washing of the coat and polishing of the fur; specific treatments against woodworms, moths, and mites; brushing and repositioning of the hair; cleaning, restoration, or creation of adequate supports or display case. The conservative intervention that should be periodically performed on each taxidermized specimen allows the protection against biodeterioration or re-infestation by parasites over time.